PENGGUNAAN KOMBINASI TITIK IKAT STASIUN GLOBAL IGS DAN TITIK IKAT STASIUN GPS REGIONAL YANG DIIKATKAN PADA ITRF-2008 DALAM PENDEFINISIAN STASIUN GNSS CORS GMU1 - Sri Rezki Artini (Jurnal Tekno Global, 2018)
The CORS GNSS station can be used as a reference point in determining relative positions in both real time and post processing. This reference point is used for the measurement of points on the surface of the earth. In this measurement requires a high accuracy that is up to a fraction of a millimeter. In this research, GNSS CORS station which is used is GNSS CORS GMU1 which has been operated since 2009 which is located in Engineering Faculty Building of Department of Geodesy Engineering (Level Three) Universitas Gadjad Mada Yogyakarta, Indonesia. This study redefined the coordinates of GNSS CORS GMU1 using GNSS observation data for seven days from July 14, 2012 until July 20, 2012 using a combination of IGS and regional global bundle points. The tipping points of IGS global station used in this research are DGAR, GUAM, IISC, KARR, KUNM, PIMO, and TOW2. While the binding point of Regional station used is BAKO, CJPR, CDNP, CSRJ, SAMP, CBAL and CBIT. Data processing using scientific software GAMIT / GLOBK. The result of this research is 3D cartesian coordinate value from GNSS CORS GMU1 station in 2012 and its position speed. Coordinate of processing result that is X (m) = -2200206,97088 m ± 26,08 mm; Y (m) = 5924895,45433 m ± 26,30 mm; Z (m) = -855932,55993 m ± 192,51 mm. It can be seen that the standard deviation resulting from the combined processing of bundle points of Global IGS and regional stations is up to millimeter fraction. Speed position of GNSS CORS GMU1 station in 2012, that is VX = 0,02907 m / year ± 0.25410 m; Vy = 0.13655 m / year ± 0.47235 m; Vz = -0.07798 m / year ± 1.39 m.Keywords: GNSS CORS GMU1 station, GPS connectivity, GAMIT software